Integration of Multimedia in Toddlers’ Education of the Al-Qur’an: A Case of Kampong Gunong Qur’anic House Belitung (EDUKASIA, 2024)
This study explores the use of multimedia in teaching the Al-Qur'an to toddlers at the Kampong Gunong Qur'anic House in Belitung. Using a qualitative case study approach, data were gathered through interviews, observations, and documents. The findings highlight the effective use of multimedia tools, particularly Syaikh Kamil El Laboudy’s murattal video, in the Tabarak method of Al-Qur'an learning. This approach successfully motivated toddlers to memorize the Al-Qur'an quickly while improving the quality of their recitation. However, the study's limitations included its focus on a single institution and the short duration of the research, which did not examine long-term effects on childhood’s cognitive and spiritual development. Despite these limitations, the study contributed valuable insights into integrating technology in early children's religious education and offered recommendations for future research on the long-term impacts of multimedia-assisted Al-Qur'an learning.